Management of Arabic Language Skills Development in Islamic Education Institutions - Bambang Irawan (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2019)
Abstract This article discusses the management of Arabic language skills development in Islamic educational institutions. Self-development management can be carried out with two models. The first is the counselling model. Counselling is an assistance service for students, both individually and in groups, in order to be able to independently and develop optimally, in the field of developing learning abilities, interest talents and language skills through various types of services and support activities. The second is a model of extra-curricular activities, namely educational activities outside the subject matter and counselling services to help develop students according to their needs and potentials through activities organised explicitly by educators and Islamic educational institutions. Keywords: Management, Development, Arabic Language Ability.